How to Curb Global Warming after 'Hopenhagen' and 'Climate-Gate' - Marco Verweij (Amsterdam Law Forum, 2010)
In November 2001, at the seventh ‘Conference of the Parties’ (to the United Nations Framework Convention on Climate Change) in Marrakech, the head of the diplomatic mission from one of the largest developing countries told me that it would be impossible to agree on a ‘second commitment period’. That was UN-speak for predicting that a successor treaty to the Kyoto Protocol (which covers the ‘first commitment period’ up to 2012) would never see the light of day. Even back then, more than three years before the Kyoto Protocol entered into force in February 2005, it was clear to at least some of the diplomats involved in the global warming-negotiations that the financial and ideological differences between governments were too vast to ever allow the emergence of a meaningful, binding, global treaty. This was worrying given that the cutbacks of greenhouse gases foreseen in the Kyoto Protocol were generally perceived as well-nigh insignificant and ‘just a first step’.